The genetics of psoriasis : selected novelties in 2008 - Pašić, Aida (Array, 2009)
Summary: The genetic background of psoriasis is clearly demonstrated by the familial occurrence, data from epidemiological studies, twin studies, and results of genome-wide scan investigations. In the last years, molecular genetics analyses have permitted new insights into psoriasis. A number of studies indicate the likely genomic location of psoriasis susceptibility genes and suggest their possible identity and function. According to current concepts, psoriasis is caused by the interplay of multiple genes and different trigger factors, and the disease is classified in the group of genetically “complex” diseases. The first associated locus (PSORS1) resides within the HLA region (6p21.3). Strong association of HLA-Cw6 allele at this locus was first reported in Finnish population over 26 years ago. However, the exact location of PSORS1 gene remains controversial due to extensive linkage disequilibrium across the region. Two genes lying within this interval have been intensively studied with respect to their role in psoriasis susceptibility: HCR and corneodesmosin (CDSN). The precise location of PSORS 1 is under intense screening. Other candidate loci identified by genetic linkage research include PSORS 2 (17q25), PSORS 3 (4q34), PSORS 4 (1q21), PSORS 5 (3q21), PSORS 6 (19p13), PSORS 7 (1p32), PSORS 8 (16q) and PSORS 9 (4q31). Despite a large body of new data, the extent of genetic heterogeneity and the role of environmental triggers and modifier genes have not yet been clarified. The isolation of novel susceptibility genes will provide an insight into the precise pathways that control the disease. Such pathways will also reveal additional candidate genes that can be tested for molecular alterations resulting in the disease